A high energy density composite positive electrode material and its preparation method and application
By developing composite positive electrode materials, using the combination of graphite conductive framework and polyanionic material, the problems of energy density limit and limited lithium resources of lithium are solved, and a battery positive electrode material with high energy density and good cycle performance are achieved.
Patent Information
- Application Number
- CN202211255335.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-10-13
AI Technical Summary
The energy density of existing lithium-ion batteries has basically reached its limit, and the lithium resources are limited and the cost is high, which has led to the bottleneck of the development of lithium-ion batteries.
A high-energy density composite cathode material was developed, including RxMy[PA]zFn/graphite, R is an alkali metal ion, M is a variable valence transition metal ion, and PA is a polyanionic monomer. This material achieves structural stability and high conductivity through the combination of graphite conductive framework and polyanionic material, and improves specific capacity and energy density.
The composite positive electrode material maintains its structural stability during electrochemical charging and discharging, significantly improving the specific capacity, energy density and cycling performance of the battery, and is suitable for high-energy density secondary battery applications.
Smart Images

Figure CN115458724B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high-energy-density composite positive electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous development of social civilization, human demand for energy is increasing day by day. However, traditional fossil energy has prominent problems such as resource depletion and environmental pollution, which seriously restrict the development of social economy. In order to solve the above problems, the development of clean energy such as solar energy, tidal energy, and wind energy is an inevitable choice. In this process, energy conversion and storage are issues that must be faced. Secondary batteries have become the most important energy conversion and storage technology due to their high efficiency, low cost, and recyclability. At present, the main secondary battery technologies include lead-acid batteries, nickel-chromium batteries, nickel-hydrogen batteries, lithium-ion batteries, etc. Among them, lithium-ion batteries have been widely used in portable electronic products, pure electric vehicles, and hybrid vehicles due to their high energy density, high operating voltage, long cycle life, and low self-discharge rate. However, the energy density of lithium-ion batteries has basically reached its limit. To break through this limit, it can only be comprehensively designed from new materials, new configurations, or from the source of energy storage mechanism.
[0003] In addition, in order to cope with the problems of limited lithium resources and high costs in lithium-ion batteries, a series of new next-generation secondary battery systems that can replace lithium-ion battery technology have been developed in recent years. Among them, elements such as sodium and potassium have similar chemical properties and excellent intercalation and deintercalation characteristics to lithium, making their corresponding battery technologies very promising alternatives to lithium-ion batteries. More importantly, they have natural advantages such as wide distribution of resources and relatively low prices. Therefore, sodium-ion batteries and potassium-ion batteries have received widespread attention from researchers. However, they started later than lithium-ion batteries, face more bottlenecks, and their energy density is also lower than that of lithium-ion batteries.
[0004] As we all know, a complete battery mainly includes a positive electrode, a negative electrode, and an electrolyte. The electrolyte mainly plays a role in connecting the positive and negative electrodes and ion transmission, and it generally does not have a direct impact on the capacity and energy density of the battery. The negative electrode usually has a higher capacity, so it is not a decisive factor in limiting the capacity and energy density of the battery. The positive electrode material is usually limited in capacity, and its reaction potential directly determines the charge and discharge potential of the whole battery. Therefore, the positive electrode material is the core component that determines the energy density of the battery.
[0005] Therefore, in order to break through the shackles of energy density, it is urgent to develop a new high-energy-density battery positive electrode material to further improve the battery's cycle performance. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a high-energy-density composite positive electrode material and a preparation method and application thereof. The composite positive electrode material maintains structural stability during the electrochemical charge and discharge process, and the secondary battery (such as an alkali metal ion battery) prepared using the composite positive electrode material has high capacity, high charge and discharge voltage platform, high energy density, high specific capacity, and good cycle performance.
[0007] The inventive concept of the present invention is: the composite positive electrode material of the present invention comprises R x M y [PA] z F n / graphite, R represents an alkali metal ion, M represents a variable valence transition metal ion, and PA represents a polyanion monomer. x M y [PA] z F n It is a typical polyanionic material that can grow in situ between graphite layers and can reversibly store alkali metal ions. Some unoccupied graphite layers can reversibly accommodate anions in the electrolyte, and the composite positive electrode material can maintain its own structural stability during the process of anion and cation deintercalation / insertion. Due to the confinement effect of graphite, R x M y [PA] z F n Controllable uniform growth improves the stability and diffusion kinetics of composite cathode materials. With the help of graphite conductive skeleton, high conductivity of composite cathode materials is achieved, which promotes electron transfer and charge transport; with the help of graphite anion storage capacity, the reactive sites of composite cathode materials are increased, and the specific capacity and energy density of composite cathode materials are improved. There are two types of energy storage reactions in composite cathode materials, of which R x M y [PA] z F n Capable of reversibly storing alkali metal ions, graphite can reversibly store anions in the electrolyte, which significantly improves the specific capacity and energy density of the electrode.
[0008] A first aspect of the present invention provides a composite cathode material with high energy density.
[0009] Specifically, a high energy density composite cathode material includes R x M y [PA] z F n / graphite;
[0010] The R x M y [PA] z Fn It is a polyanionic material and exists between graphite layers;
[0011] Wherein, R represents an alkali metal ion;
[0012] M is a variable valence transition metal ion;
[0013] PA represents polyanionic monomer;
[0014] Among them, 1≤x≤15; 1≤y≤15; 1≤z≤15; 0≤n≤15.
[0015] Preferably, the R is at least one of Li, Na, and K. That is, in the composite positive electrode material, R represents one or a combination of Li, Na, and K alkali metal ions.
[0016] Preferably, M is one or a combination of variable-valence transition metals selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn.
[0017] Preferably, the PA represents an anion formed by at least one of B, C, N, Si, P, S and O.
[0018] Further preferably, the PA is BO2 - , BO3 3- 、B4O7 2- 、CO3 2- 、C2O4 2- 、NO3 - 、SiO4 4- PO2 - PO3 3- PO4 3- 、P2O7 4- 、P3O 10 5- 、SO3 2- 、SO4 2- 、S2O3 2- 、S2O7 2- One or a combination of anions.
[0019] Preferably, 1≤x≤10; 1≤y≤10; 1≤z≤10; 0≤n≤10. When n is 0, it means that the composite positive electrode material does not contain F.
[0020] Preferably, the composite positive electrode material includes at least one of KVPO4F / graphite, KFePO4F / graphite, and KTiPO4F / graphite.
[0021] The second aspect of the present invention provides a method for preparing the above-mentioned high energy density composite positive electrode material.
[0022] Specifically, a method for preparing a high energy density composite positive electrode material comprises the following steps:
[0023] (1) mixing a transition metal source and graphite, reacting, and obtaining a product;
[0024] (2) subjecting the product obtained in step (1), a polyanion monomer source, and an alkali metal ion source to a solvothermal reaction to obtain a precipitate;
[0025] (3) Calcining the precipitate of step (2) to obtain the composite positive electrode material.
[0026] Preferably, in step (1), the transition metal source includes at least one of a titanium source, a vanadium source, a chromium source, a manganese source, an iron source, a cobalt source, a nickel source, a copper source, and a zinc source.
[0027] Further preferably, the titanium source includes at least one of elemental titanium, titanium trioxide, titanium dioxide, titanium (III) sulfate, titanium (IV) sulfate, titanium phosphate, potassium fluorotitanate, hexafluorotitanic acid, tetrabutyl titanate, tetraethyl titanate, isopropyl titanate, titanium tetrachloride, titanium trichloride, titanium dihydride, ammonium fluorotitanate, titanium tetrafluoride, dichlorobis(acetylacetonato)isopropyl titanate or its hydrate. More preferably, the titanium source is titanium tetrachloride.
[0028] Further preferably, the vanadium source includes at least one of elemental vanadium, vanadium trioxide, vanadium dioxide, vanadium pentoxide, vanadium difluoride, vanadium trifluoride, vanadium tetrafluoride, vanadium pentafluoride, vanadium oxyfluoride, vanadium dichloride, vanadium trichloride, vanadium tetrachloride, vanadium oxychloride, vanadium dibromide, vanadium tribromide, vanadium tetrabromide, ammonium metavanadate, potassium orthovanadate, potassium metavanadate, vanadium acetylacetonate, vanadium oxyacetonate, triisopropoxy vanadium oxide, tripropanol vanadium oxide or its hydrate. More preferably, the vanadium source is vanadium trichloride.
[0029] Further preferably, the chromium source comprises at least one of elemental chromium, chromium acetate, chromium fluoride, chromium sulfate, chromium (II) chloride, chromium (III) chloride, chromium oxide, chromium nitride, chromium acetate, chromium nitrate or hydrates thereof. More preferably, the chromium source is chromium (II) chloride or chromium (III) chloride.
[0030] Further preferably, the manganese source includes at least one of elemental manganese, manganese oxide, manganese dioxide, manganese tetraoxide, manganese (II) fluoride, manganese (III) fluoride, manganese (II) chloride, manganese (III) chloride, manganese bromide, manganese carbonate, manganese nitrate, manganese sulfate, manganese phosphate, manganese dihydrogen phosphate, manganese acetylacetonate, manganese formate, manganese (II) acetate, manganese (III) acetate, manganese oxalate or a hydrate thereof. More preferably, the manganese source is manganese chloride.
[0031] Further preferably, the iron source includes at least one of elemental iron, ferric oxide, ferrous oxide, ferrous hydroxide, ferric hydroxide, ferrous fluoride, ferric fluoride, ferrous chloride, ferric chloride, ferric bromide, ferric bromide, ferric formate, ferrous acetate, ferrous nitrate, ferrous sulfate, ferric nitrate, ferric sulfate, ferric acetylacetonate, ferrous oxalate, ferric oxalate or their hydrates. More preferably, the iron source is ferric chloride.
[0032] Further preferably, the cobalt source includes at least one of elemental cobalt, cobalt monoxide, cobalt trioxide, cobalt tetraoxide, cobalt (II) hydroxide, cobalt (III) hydroxide, cobalt (II) fluoride, cobalt (III) fluoride, cobalt (II) chloride, cobalt (III) chloride, cobalt bromide, cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate, cobalt oxalate, hexaaminocobalt chloride, cobalt acetylacetonate or their hydrates. More preferably, the cobalt source is cobalt chloride or cobalt oxalate.
[0033] Further preferably, the nickel source includes at least one of elemental nickel, nickel oxide, nickel oxide, nickel hydroxide, nickel hydroxide, nickel fluoride, nickel chloride, nickel bromide, nickel nitrate, nickel carbonate, nickel sulfate, nickel acetate, nickel oxalate, nickel bis(hexafluoroethylacetone), nickel sulfamate, basic nickel carbonate, nickel acetylacetonate dihydrate, nickel trifluoromethanesulfonate, nickel benzenesulfonate, nickel acetylacetonate, nickel fluoroborate or its hydrate. More preferably, the nickel source is nickel chloride or nickel sulfate.
[0034] Further preferably, the copper source is at least one of elemental copper, cuprous oxide, cupric oxide, copper hydroxide, copper fluoride, copper chloride, copper bromide, copper carbonate, basic copper carbonate, copper nitrate, copper sulfate, copper acetate, copper oxalate, copper tartrate, copper citrate, copper fluoroborate, copper acetylacetonate, copper gluconate, copper phosphate or a hydrate thereof. More preferably, the copper source is copper chloride or copper phosphate.
[0035] Further preferably, the zinc source includes at least one of elemental zinc, zinc oxide, zinc hydroxide, zinc fluoride, zinc chloride, zinc bromide, zinc iodide, zinc sulfate, zinc nitrate, zinc carbonate, zinc acetate, zinc oxalate, zinc citrate, zinc fluoroborate, zinc tartrate, zinc borate, zinc metaborate, zinc acetylacetonate, zinc gluconate or a hydrate thereof. More preferably, the zinc source is zinc chloride.
[0036] Preferably, in step (1), the ratio of the amount of the transition metal source to the graphite can be any value. Further preferably, the mass ratio of the transition metal source to the graphite is 1:(0.5-2.5); more preferably, the mass ratio of the transition metal source to the graphite is 1:(0.8-1.5).
[0037] Preferably, in step (1), the reaction temperature is 80-1200°C; further preferably, the reaction temperature is 100-1200°C; more preferably, the reaction temperature is 100-600°C.
[0038] Preferably, in step (1), the reaction time is more than 10 minutes; further preferably, the reaction time is 10 minutes to 6 hours; more preferably, the reaction time is 1 hour to 5 hours.
[0039] Preferably, in step (1), the reaction is carried out in a reactor and the reactor is sealed during the reaction.
[0040] Preferably, in step (2), the polyanion monomer source includes at least one of boric acid, fluoroboric acid, potassium fluoroborate, ammonium borate, lithium carbonate, sodium carbonate, potassium carbonate, lithium nitrate, sodium nitrate, potassium nitrate, silicic acid, fluorosilicic acid, potassium fluorosilicate, phosphoric acid, lithium phosphate, sodium phosphate, potassium phosphate, sulfuric acid, lithium sulfate, sodium phosphate, potassium sulfate, oxalic acid, potassium oxalate, potassium hydrogen oxalate, ammonium oxalate, diethyl oxalate or its hydrate.
[0041] More preferably, the polyanion monomer source is at least one of boric acid, oxalic acid, phosphoric acid, sulfuric acid and silicic acid.
[0042] Preferably, in step (2), the alkali metal ion source includes at least one of a lithium source, a sodium source or a potassium source.
[0043] Further preferably, the lithium source includes at least one of lithium fluoride, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium acetate, lithium salicylate, lithium acetoacetate, lithium carbonate, lithium trifluoromethanesulfonate, lithium dodecyl sulfate, lithium citrate, lithium bis(trimethylsilyl)amide, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl)imide, or a hydrate thereof.
[0044] Further preferably, the sodium source includes at least one of sodium chloride, sodium fluoride, sodium sulfate, sodium carbonate, sodium phosphate, sodium nitrate, sodium difluorooxalatoborate, sodium pyrophosphate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, trisodium citrate, sodium metaborate, sodium borate, sodium molybdate, sodium tungstate, sodium bromide, sodium nitrite, sodium iodate, sodium iodide, sodium silicate, sodium lignin sulfonate, sodium hexafluorophosphate, sodium oxalate, sodium aluminate, sodium methane sulfonate, sodium acetate, sodium dichromate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(trifluoromethanesulfonyl)imide or a hydrate thereof.
[0045] Further preferably, the potassium source includes at least one of potassium carbonate, potassium acetate, potassium nitrite, potassium fluoroborate, potassium bromide, potassium sulfate, potassium oxalate, potassium persulfate, potassium hydroxide, potassium pyrosulfate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium pyrosulfite, potassium pyrophosphate, potassium chromium sulfate, potassium hydrogen tartrate, potassium dichromate, potassium hydrogen phthalate, potassium hydrogen oxalate, potassium sulfite, potassium sorbate, potassium fluorosilicate, tripotassium phosphate, potassium gluconate, potassium oleate or a hydrate thereof.
[0046] More preferably, the alkali metal ion source is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium fluoride, sodium fluoride, potassium fluoride or their hydrates.
[0047] Preferably, when the alkali metal ion source is added in step (2), a fluorine source is also added, or in step (3) of calcination, the precipitate is first mixed with the fluorine source and then calcined.
[0048] Preferably, the fluorine source includes at least one of potassium fluoride, sodium fluoride, lithium fluoride, potassium fluoroborate, potassium fluorosilicate, potassium tantalate, ammonium fluoroborate, diethyl fluoromalonate, potassium fluorotitanate, 3,5-difluorobenzylamine, 2,6-difluorobenzoic acid, 2-chloro-4-fluorobenzoic acid, 3-fluoro-5-bromoaniline, heptafluorobutyric acid, m-trifluoromethylcinnamoyl chloride or perfluorooctanoic acid.
[0049] More preferably, the fluorine source is lithium fluoride, sodium fluoride or potassium fluoride.
[0050] Preferably, in step (2), the solvothermal reaction refers to a solvothermal reaction of mixing the product obtained in step (1), a polyanion monomer source, an alkali metal ion source and a solvent.
[0051] Preferably, the solvent comprises at least one of water, methanol, ethanol, acetone, ethylene glycol or pyridine. Further preferably, the solvent is ethylene glycol.
[0052] Preferably, in step (2), the temperature of the solvent thermal reaction is 80-280°C; further preferably, the temperature of the solvent thermal reaction is 100-250°C.
[0053] Preferably, in step (2), the solvent thermal reaction time is more than 0.5 hours; further preferably, the solvent thermal reaction time is 0.5-28 hours; more preferably, the solvent thermal reaction time is 5-24 hours.
[0054] Preferably, in step (2), the precipitate is separated by centrifugation or filtration, and then the precipitate is washed with water or anhydrous ethanol and then vacuum dried.
[0055] Preferably, the vacuum drying is carried out under the conditions of pressure ≤30 kPa and temperature of room temperature-120°C for 5-24 h; further preferably, the vacuum drying is carried out under the conditions of pressure ≤20 kPa and temperature of room temperature-120°C for 10-24 h.
[0056] Preferably, in step (2), the amounts of the product obtained in step (1), the polyanion monomer source, and the alkali metal ion source can be adjusted according to actual conditions and can be any amount relationship.
[0057] Preferably, the alkali metal ion source can also be mixed with the precipitate before calcination in step (3), and then calcined. That is, the alkali metal ion source can be added before the solvent thermal reaction or before calcination.
[0058] Preferably, in step (3), the calcination temperature is 350-1600°C; further preferably, the calcination temperature is 400-1500°C; more preferably, the calcination temperature is 400-600°C.
[0059] Preferably, in step (3), the calcination time is more than 10 minutes; further preferably, the calcination time is 10 minutes to 72 hours; more preferably, the calcination time is 1-18 hours.
[0060] The third aspect of the present invention provides the application of the above-mentioned high energy density composite positive electrode material.
[0061] Specifically, the composite positive electrode material is used in batteries, electric vehicles or energy storage power stations.
[0062] Preferably, the battery is a secondary battery, such as an alkali metal ion battery.
[0063] A secondary battery comprises the composite positive electrode material.
[0064] Preferably, the energy density of the secondary battery is not less than 100Wh / kg; further preferably, the energy density of the secondary battery is not less than 120Wh / kg, for example, not less than 150Wh / kg, 180Wh / kg, or 200Wh / kg.
[0065] Preferably, the specific capacity of the secondary battery is not less than 100 mAh / g; further preferably, the specific capacity of the secondary battery is not less than 110 mAh / g, for example, not less than 120 mAh / g, 130 mAh / g.
[0066] Preferably, the number of cycles when the capacity of the secondary battery decays to 85% is not less than 300 times; further preferably, the number of cycles when the capacity of the secondary battery decays to 85% is not less than 400 times; more preferably, the number of cycles when the capacity of the secondary battery decays to 85% is not less than 500 times.
[0067] Preferably, a secondary battery comprises a positive electrode, an electrolyte, a separator, and a negative electrode;
[0068] The positive electrode includes a positive electrode current collector and a positive electrode active material, and the positive electrode active material includes the composite positive electrode material.
[0069] Preferably, the secondary battery further includes a battery casing for packaging.
[0070] Preferably, the negative electrode comprises a negative electrode active material.
[0071] Preferably, the negative electrode further comprises a negative electrode current collector. When the negative electrode active material is metal, a negative electrode current collector is not required, and when the negative electrode active material is not metal foil, a negative electrode current collector is required.
[0072] Preferably, the negative electrode further comprises at least one of a conductive agent or a binder. The conductive agent and the binder are not particularly limited, the conductive agent is a conductive agent conventionally used in battery electrodes, and the binder can be the same as the binder used in the positive electrode.
[0073] Preferably, the negative electrode active material includes at least one of carbon materials, metal oxides, sulfides, selenides, tellurides, metals and their alloys; further preferably, the negative electrode active material is at least one of potassium, graphite, activated carbon, cobalt oxide, iron sulfide, tin selenide, tin telluride, antimony, tin, tin-antimony alloy, potassium titanate or potassium stannate.
[0074] Preferably, the negative electrode current collector includes one of aluminum, copper, iron, tin, zinc, nickel, titanium, manganese, or an alloy thereof.
[0075] Preferably, the positive electrode current collector includes one of aluminum, copper, iron, tin, zinc, nickel, titanium, manganese, chromium, or an alloy thereof.
[0076] Further preferably, the negative electrode current collector is copper or aluminum.
[0077] Further preferably, the positive electrode current collector is one of aluminum, titanium, copper, chromium, or an alloy thereof or a composite material thereof.
[0078] Preferably, the electrolyte is a mixed solution of an alkali metal salt electrolyte and a solvent.
[0079] In the present invention, the solvent in the electrolytic solution is not particularly limited as long as the solvent can dissociate the electrolyte into cations and anions, and the cations and anions can migrate freely.
[0080] Preferably, the solvent in the electrolyte includes at least one of esters, sulfones, ethers, nitriles or ionic liquids.
[0081] Further preferably, the solvent in the electrolyte includes propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate (MF), methyl acetate (MA), N,N-dimethylacetamide (DMA), fluoroethylene carbonate (FEC), methyl propionate (MP), ethyl propionate (EP), ethyl acetate (EA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), 1,3-dioxolane (DOL), 4-methyl-1,3-dioxolane (4MeDOL), dimethoxymethane (DMM), 1,2-dimethoxypropane (DMP), triethylene glycol dimethyl ether (DG), dimethyl sulfone (MSM), dimethyl ether (DME), vinyl sulfite (ES), propylene sulfite (PS), dimethyl sulfite (DMS), sulfite Diethyl ester (DES), crown ether (12-crown-4), 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-propyl-3-methylimidazolium hexafluorophosphate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-1-methylimidazolium hexafluorophosphate, 1 -butyl-1-methylimidazole-tetrafluoroborate, 1-butyl-1-methylimidazole-bis(trifluoromethylsulfonyl)imide salt, N-butyl-N-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, 1-butyl-1-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl-N-propylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl, propylpiperidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl, butylpiperidine-bis(trifluoromethylsulfonyl)imide salt.
[0082] More preferably, the solvent in the electrolyte is at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl ether (DME), and ethyl methyl carbonate (EMC).
[0083] In the present invention, the alkali metal salt as the electrolyte in the electrolytic solution is not particularly limited as long as it can be dissociated into cations and anions.
[0084] Preferably, the alkali metal salt electrolyte in the electrolyte includes lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium acetate, lithium salicylate, lithium acetoacetate, lithium carbonate, lithium trifluoromethanesulfonate, lithium dodecyl sulfate, lithium citrate, lithium bis(trimethylsilyl)amide, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl)imide, sodium chloride, sodium fluoride, sodium sulfate, sodium carbonate, sodium phosphate, sodium nitrate, sodium difluorooxalatoborate, sodium pyrophosphate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, trisodium citrate, sodium metaborate, sodium borate, sodium molybdate, sodium tungstate, sodium bromide, sodium nitrite, sodium iodate, sodium iodide, sodium silicate, sodium ligninsulfonate, sodium hexafluorophosphate, sodium oxalate, sodium aluminate, sodium methanesulfonate, At least one of sodium acetate, sodium dichromate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(trifluoromethanesulfonyl)imide, potassium hexafluorophosphate, potassium chloride, potassium fluoride, potassium sulfate, potassium carbonate, potassium phosphate, potassium nitrate, potassium difluorooxalatoborate, potassium pyrophosphate, potassium dodecylbenzenesulfonate, potassium dodecyl sulfate, tripotassium citrate, potassium metaborate, potassium borate, potassium molybdate, potassium tungstate, potassium bromide, potassium nitrite, potassium iodate, potassium iodide, potassium silicate, potassium ligninsulfonate, potassium oxalate, potassium aluminate, potassium methanesulfonate, potassium acetate, potassium dichromate, potassium hexafluoroarsenate, potassium tetrafluoroborate, potassium perchlorate, potassium trifluoromethanesulfonyl imide (KTFSI), KCF3SO3, and KN(SO2CF3)2.
[0085] Further preferably, the alkali metal salt electrolyte is at least one of lithium hexafluorophosphate, sodium hexafluorophosphate, potassium hexafluorophosphate, KCF3SO3, and potassium trifluoromethanesulfonyl imide (KTFSI).
[0086] Further preferably, the concentration of the alkali metal salt electrolyte in the electrolyte is 0.1-12 mol / L; more preferably, the concentration of the alkali metal salt electrolyte in the electrolyte is 0.1-10 mol / L; more preferably, the concentration of the alkali metal salt electrolyte in the electrolyte is 0.5-3 mol / L.
[0087] Preferably, the electrolyte further comprises an additive, and the additive is used to improve the electrochemical stability of the alkali metal ion battery.
[0088] Preferably, the additive comprises at least one of ester, sulfone, ether, nitrile or olefin organic additives.
[0089] Further preferably, the additive includes fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, propylene sulfate, ethylene sulfate, vinyl sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite, ethylene sulfite, methyl chloroformate, dimethyl sulfoxide, anisole, acetamide, diazine, meta-diazine, crown ether 12-crown-4, crown ether 18-crown- 6. At least one of 4-fluoroanisole, fluorinated chain ether, difluoromethylethylene carbonate, trifluoromethylethylene carbonate, chloroethylene carbonate, bromoethylene carbonate, trifluoroethylphosphonic acid, bromobutyrolactone, fluoroacetoxyethane, phosphate ester, phosphite, phosphazene, ethanolamine, carbodimethylamine, cyclobutyl sulfone, 1,3-dioxolane, acetonitrile, long-chain olefins, aluminum oxide, magnesium oxide, barium oxide, sodium carbonate, calcium carbonate, carbon dioxide, sulfur dioxide, and lithium carbonate.
[0090] Preferably, the additive is added in an amount of 0.1-22 wt % in the electrolyte, more preferably, the additive is added in an amount of 0.1-20 wt % in the electrolyte, and specifically, the additive may be added in an amount of 1-20 wt % in the electrolyte.
[0091] Preferably, the membrane is made of an insulating porous polymer film or an inorganic porous film, and at least one of a porous polypropylene film, a porous polyethylene film, a porous composite polymer film, glass fiber paper or a porous ceramic membrane can be selected.
[0092] Further preferably, the membrane is made of at least one of glass fiber paper and porous ceramic membrane.
[0093] Preferably, the positive electrode further includes a binder.
[0094] Preferably, there is no particular limitation on the binder, and any binder commonly used in the art may be used.
[0095] Further preferably, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, carboxymethyl cellulose, SBR (styrene butadiene rubber), and polyolefins; more preferably, the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, and SBR (styrene butadiene rubber).
[0096] Preferably, in the positive electrode active material, by weight, the composite positive electrode material is 70-99 parts, and the binder is 1-30 parts; further preferably, in the positive electrode active material, by weight, the composite positive electrode material is 80-99 parts, and the binder is 1-20 parts.
[0097] A method for preparing a secondary battery comprises the following steps:
[0098] The composite positive electrode material is prepared into a slurry, and coated on the surface of the positive electrode current collector to obtain a positive electrode;
[0099] The positive electrode and the negative electrode, the electrolyte and the separator are assembled to obtain the secondary battery.
[0100] Preferably, a method for preparing a secondary battery comprises the following steps:
[0101] Preparation of negative electrode: cutting metal foil to serve as negative electrode and negative electrode current collector, or mixing negative electrode active material, conductive agent and binder into slurry to prepare negative electrode active material slurry, coating the negative electrode active material slurry on the surface of negative electrode current collector, drying and cutting to obtain negative electrode;
[0102] Preparing an electrolyte: mixing an alkali metal salt electrolyte with a solvent to prepare an electrolyte;
[0103] Preparing the diaphragm: cutting the diaphragm to obtain the diaphragm;
[0104] Prepare the positive electrode: mix the composite positive electrode material, binder and solvent to prepare positive electrode active material slurry, then apply the positive electrode active material slurry on the surface of the positive electrode current collector, dry and cut to obtain the positive electrode;
[0105] Assembling the battery: Assembling the negative electrode, electrolyte, separator and positive electrode to obtain the secondary battery.
[0106] The negative electrode, electrolyte, separator and positive electrode may be prepared in any order.
[0107] The above-mentioned secondary battery is a battery having a high energy density.
[0108] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0109] (1) The composite positive electrode material of the present invention comprises R x M y [PA] z F n / graphite (where 1≤x≤15; 1≤y≤15; 1≤z≤15; 0≤n≤15), R represents an alkali metal ion, M is a variable valence transition metal ion, and PA represents a polyanion monomer. x M y [PA] z F n It is a typical polyanionic material that can grow in situ between graphite layers and can reversibly store alkali metal ions. Some unoccupied graphite layers can reversibly accommodate anions in the electrolyte, and the composite positive electrode material can maintain its own structural stability during the anion and cation deintercalation / insertion process. Due to the confinement effect of graphite, Rx M y [PA] z F n Controllable uniform growth improves the stability and diffusion kinetics of composite cathode materials. With the help of graphite conductive skeleton, high conductivity of composite cathode materials is achieved, which promotes electron transfer and charge transport; with the help of graphite anion storage capacity, the reactive sites of composite cathode materials are increased, and the specific capacity and energy density of composite cathode materials are improved.
[0110] (2) There are two types of energy storage reactions in the composite cathode material of the present invention, R x M y [PA] z F n Capable of reversibly storing alkali metal ions, graphite can reversibly store anions in the electrolyte, which significantly improves the specific capacity and energy density of the electrode.
[0111] (3) The preparation method of the composite positive electrode material of the present invention decomposes the complex composite positive electrode material synthesis into several simple steps through high temperature reaction, solvent thermal reaction and calcination, so that the process is simple and easy to operate, the cost of raw materials required is low, the equipment requirements are low, and it is environmentally friendly and suitable for large-scale industrial production.
[0112] (4) The composite positive electrode material of the present invention is applied to the fields of batteries, electric vehicles or energy storage power stations. Due to the two types of energy storage reactions existing in the composite positive electrode material during the charge and discharge process, the composite positive electrode material maintains excellent structural stability during the charge and discharge cycle, and does not require a conductive agent in the traditional sense during the positive electrode preparation process. Therefore, the secondary battery (such as an alkali metal ion battery) assembled from the composite positive electrode material has a high specific capacity, a long cycle life, and a high energy density, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0113] Figure 1 This is a schematic diagram of the structure of the composite positive electrode material prepared in Example 1 of the present invention;
[0114] Figure 2 This is the XRD diagram of the composite positive electrode material prepared in Example 1 of the present invention;
[0115] Figure 3 This is a schematic diagram of the structure of a secondary battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0116] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0117] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0118] Example 1: Preparation of composite positive electrode material and secondary battery
[0119] A high energy density composite positive electrode material comprises KVPO4F / graphite, wherein KVPO4F exists between graphite layers.
[0120] A method for preparing a high energy density composite positive electrode material comprises the following steps:
[0121] (1) Weigh 0.4 g of graphite and 3.8 g of VCl3 into a high-temperature and high-pressure reactor, mix and stir evenly, place the high-temperature and high-pressure reactor in a high-temperature furnace protected by argon gas, react at 600° C. for 5 hours (this process is called high-temperature and high-pressure reaction), and cool to obtain a product;
[0122] (2) dispersing the product obtained in step (1) in 30 mL of ethylene glycol, adding 2.6 mL of 85 wt% H3PO4 solution, mixing thoroughly, and then loading into a 50 mL polytetrafluoroethylene-lined reactor, sealing the reactor and placing it in a stainless steel shell, and placing it in a 180° C. oven for hydrothermal reaction for 24 hours (this process is a solvent thermal reaction); after the reactor is cooled, collecting the precipitate, and washing the precipitate with water and ethanol;
[0123] (3) The precipitate obtained in step (2) was mixed with 1.67 g of potassium fluoride and subjected to high-speed ball milling until fully mixed; the mixed mixture was placed in a high-temperature furnace protected by argon gas and calcined at 650° C. for 8 hours (this process is called calcination reaction) to obtain a composite positive electrode material.
[0124] Figure 1 Schematic diagram of the structure of the composite positive electrode material prepared in Example 1 of the present invention; Figure 1 It can be seen that KVPO4F exists between graphite layers.
[0125] Figure 2 is the XRD pattern of the composite positive electrode material prepared in Example 1 of the present invention; Figure 2 ( Figure 2 The horizontal axis "2theta (degree)" represents 2θ (degree), and the vertical axis "Intensity" represents intensity). It can be seen that the composite positive electrode material prepared in Example 1 contains KVPO4F and graphite.
[0126] A secondary battery comprises a positive electrode, an electrolyte, a separator and a negative electrode;
[0127] The positive electrode includes a positive electrode current collector (aluminum) and a positive electrode active material, and the positive electrode active material is the above-mentioned composite positive electrode material (KVPO4F / graphite);
[0128] The electrolyte is a mixture of potassium hexafluorophosphate, ethylene carbonate and dimethyl carbonate, the volume ratio of ethylene carbonate to dimethyl carbonate in the electrolyte is 1:1, and the concentration of potassium hexafluorophosphate is 1 mol / L;
[0129] The diaphragm is a glass fiber diaphragm;
[0130] The negative electrode is potassium metal.
[0131] The method for preparing the secondary battery comprises the following steps:
[0132] Preparation of negative electrode: Press potassium metal into thin sheets, cut into discs with a diameter of 12 mm to prepare the negative electrode;
[0133] Preparation of electrolyte: adding potassium hexafluorophosphate electrolyte to a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, stirring and dissolving, to prepare an electrolyte with a concentration of 1 mol / L;
[0134] Preparation of the diaphragm: Cut the glass fiber diaphragm into discs with a diameter of 16 mm and dry them to obtain the diaphragm;
[0135] Preparation of positive electrode: Add polyvinylidene fluoride to the above composite positive electrode material (KVPO4F / graphite) and mix thoroughly. The mass ratio of the composite positive electrode material to polyvinylidene fluoride is 9:1. Add 2 mL of nitrogen methyl pyrrolidone and mix thoroughly to form a uniform positive electrode active material slurry. Clean the positive electrode collector, and then evenly apply the positive electrode active material slurry on the surface of the positive electrode collector (aluminum). After drying, cut it into a positive electrode with a diameter of 10 mm.
[0136] Assembling the battery: In a glove box protected by inert gas (nitrogen), the above-mentioned negative electrode, electrolyte, separator and positive electrode are tightly stacked in sequence, the electrolyte is dripped to completely soak the separator, and then the stacked part is encapsulated into a button battery casing to complete the battery assembly and prepare a secondary battery.
[0137] Figure 3 This is a schematic diagram of the structure of a secondary battery prepared in Example 1 of the present invention. Figure 3 100 represents the positive electrode current collector, 200 represents the positive electrode active material, 300 represents the electrolyte, 400 represents the separator, and 500 represents the negative electrode.
[0138] Example 2-100: Preparation of composite positive electrode material
[0139] Embodiment 2-100 is an embodiment of the preparation of a composite positive electrode material, wherein Embodiment 2-7 only changes the type of transition metal source compared with Embodiment 1; Embodiment 8-12 only changes the type of alkali metal ion source compared with Embodiment 1; Embodiment 13-27 only changes the type of polyanion monomer source compared with Embodiment 1; Embodiment 28-29 only changes the type of fluorine source compared with Embodiment 1; Embodiment 30-37 only changes the amount of graphite added compared with Embodiment 1; Embodiment 38-47 only changes the high temperature and high pressure reaction temperature compared with Embodiment 1; Embodiment 48-55 only changes the high temperature and high pressure reaction time compared with Embodiment 1; Embodiment 56-65 only changes the solvent thermal reaction temperature compared with Embodiment 1; Embodiment 66-73 only changes the solvent thermal reaction time compared with Embodiment 1; Embodiment 74-79 only changes the type of solvent for the solvent thermal reaction compared with Embodiment 1; Embodiment 80-90 only changes the calcination temperature compared with Embodiment 1; Embodiment 91-100 only changes the calcination time compared with Embodiment 1. The specific changed process parameters are shown in Table 1.
[0140] Table 1: Preparation of composite cathode materials with different process parameters
[0141]
[0142]
[0143]
[0144] Comparative Example 1
[0145] Compared with Example 1, the difference of Comparative Example 1 is that in the preparation process of the composite positive electrode material, an equal amount of hard carbon is used to replace the graphite in Example 1, and the rest of the process is the same as Example 1. That is, in Comparative Example 1, a secondary battery is prepared using the composite positive electrode material prepared in Comparative Example 1 according to the method of Example 1.
[0146] Comparative Example 2
[0147] Compared with Example 1, the difference of Comparative Example 2 is that in the preparation process of the composite positive electrode material, an equal amount of soft carbon is used to replace the graphite in Example 1, and the rest of the process is the same as Example 1. That is, in Comparative Example 2, the composite positive electrode material prepared in Comparative Example 2 is used to prepare a secondary battery according to the method of Example 1.
[0148] The electrochemical properties (specific capacity, number of cycles when the capacity decays to 85%, and energy density) of the secondary batteries prepared in Example 1 and Comparative Example 1 were tested (the test process was constant current charge and discharge at a current density of 0.5 A / g). The results are shown in Table 2.
[0149] Table 2: Comparison of performance of secondary batteries prepared in Example 1 and Comparative Example 1
[0150]
[0151]
[0152] It can be seen from Table 2 that the composite positive electrode material prepared in Example 1 has higher specific capacity, higher energy density, and better cycle stability when used in secondary batteries. That is, in the preparation process of the composite positive electrode material, the composite positive electrode material prepared by using graphite instead of hard carbon or soft carbon has better electrochemical performance.
[0153] In addition, after embodiments 2-100 of the present invention are assembled into secondary batteries in the manner of embodiment 1, the specific capacity, energy density, and cycle stability of the corresponding secondary batteries are equivalent to the specific capacity, energy density, and cycle stability of the corresponding secondary batteries in embodiment 1.
[0154] Examples 101-105: Preparation of secondary batteries
[0155] The secondary battery preparation process of Examples 101-105 is the same as that of Example 1, and the only difference is the type of binder. Please refer to Table 3 for details.
[0156] Table 3: Comparison of electrochemical performance of secondary batteries with different binder types
[0157]
[0158] It can be seen from Table 3 that when the binder used is polyvinylidene fluoride, carboxymethyl cellulose, SBR, and polytetrafluoroethylene, the corresponding electrochemical performance of the secondary battery has obvious advantages, especially when the binder is polyvinylidene fluoride, the corresponding electrochemical performance of the secondary battery is better.
[0159] Examples 106-110: Preparation of secondary batteries
[0160] The secondary battery preparation process of Examples 106-110 is the same as that of Example 1, the only difference being the different ratios of the amount (mass) of the composite positive electrode material and the binder, see Table 4 for details.
[0161] Table 4: Comparison of electrochemical performance of secondary batteries corresponding to different ratios of composite positive electrode materials and binder dosage
[0162]
[0163] It can be seen from Table 4 that when the ratio of the composite positive electrode material to the binder is not less than 8:2, the corresponding secondary battery has excellent electrochemical performance.
[0164] Examples 111-117: Preparation of secondary batteries
[0165] The secondary battery preparation process of Examples 111-117 is the same as that of Example 1, and the only difference is that the positive electrode current collector is different. For details, see Table 5.
[0166] Table 5: Comparison of electrochemical performance of secondary batteries with different positive current collectors
[0167]
[0168]
[0169] It can be seen from Table 5 that when the positive electrode current collector is aluminum, titanium, nickel, chromium or copper, the corresponding electrochemical performance of the secondary battery has obvious advantages, especially when the positive electrode current collector is aluminum or titanium, the effect is better.
[0170] Examples 118-122: Preparation of secondary batteries
[0171] The secondary battery preparation process of Examples 118-122 is the same as that of Example 1, the only difference being that the alkali metal salt electrolyte in the electrolyte is different, see Table 6 for details.
[0172] Table 6: Comparison of electrochemical performance of secondary batteries corresponding to alkali metal salt electrolytes in different electrolytes
[0173]
[0174] It can be seen from Table 6 that when the alkali metal salt electrolyte in the electrolyte is KPF6, KCF3SO3 or KTFSI, the electrochemical performance of the corresponding secondary battery has obvious advantages, especially when the alkali metal salt electrolyte is KPF6, the effect is better.
[0175] Examples 123-130: Preparation of secondary batteries
[0176] The secondary battery preparation process of Examples 123-130 is the same as that of Example 1, and the only difference is the type of solvent in the electrolyte. Please refer to Table 7 for details.
[0177] Table 7: Comparison of electrochemical performance of secondary batteries corresponding to different types of electrolyte solvents
[0178]
[0179] It can be seen from Table 7 that when the solvent in the electrolyte is EC:DMC, EC:PC, EC:EMC, EC:DEC, EC:DEC:EMC or DME, the corresponding secondary battery electrochemical performance has obvious advantages, especially when the solvent is EC:DMC, the effect is better.
[0180] Examples 131-136: Preparation of secondary batteries
[0181] The secondary battery preparation process of Examples 131-136 is the same as that of Example 1, the only difference being the different concentrations of the alkali metal salt electrolyte, see Table 8 for details.
[0182] Table 8: Comparison of electrochemical performance of secondary batteries corresponding to different alkali metal salt electrolyte concentrations in the electrolyte (M represents mol / L)
[0183]
[0184]
[0185] It can be seen from Table 8 that when the concentration of alkali metal salt electrolyte in the electrolyte is 0.5-3M, the electrochemical performance of the corresponding secondary battery has obvious advantages, especially when the solvent is an alkali metal salt electrolyte with a concentration of 1-2M, the effect is better.
[0186] Examples 137-140: Preparation of secondary batteries
[0187] The secondary battery preparation process of Examples 137-140 is the same as that of Example 1, and the only difference is that the secondary battery separator is different. Please refer to Table 9 for details.
[0188] Table 9: Comparison of electrochemical performance of secondary batteries with different separators
[0189]
[0190] It can be seen from Table 9 that when the diaphragm is a glass fiber diaphragm or a porous ceramic diaphragm, the electrochemical performance of the corresponding secondary battery has obvious advantages, especially when the diaphragm is a glass fiber diaphragm, the effect is better.
[0191] Examples 141-152: Preparation of secondary batteries
[0192] The secondary battery preparation process of Examples 141-152 is the same as that of Example 1, and the only difference is that the negative electrode active materials of the secondary batteries are different. For details, please refer to Table 10.
[0193] Table 10: Comparison of electrochemical performance of secondary batteries with different negative electrode active materials
[0194]
[0195] It can be seen from Table 10 that when the negative electrode active material is potassium, graphite, activated carbon, cobalt oxide, iron sulfide, tin selenide, tin telluride, antimony, tin, tin-antimony alloy, potassium titanate or potassium stannate, the corresponding secondary battery electrochemical performance has obvious advantages, especially when the negative electrode active material is potassium, the effect is better.
Claims
1. A composite positive electrode material, characterized in that: Including R x M y [PA] z F n / graphite; The R x M y [PA] z F n It is a polyanionic material, grown in situ between graphite layers; Wherein, R represents an alkali metal ion; M is a variable valence transition metal ion; PA represents polyanionic monomer; Among them, 1≤x≤15; 1≤y≤15; 1≤z≤15; 0≤n≤15; The M is one or a combination of variable valence transition metals selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn; The PA represents an anion formed by at least one of B, C, N, Si, P, and S and O.
2. The composite positive electrode material according to claim 1, characterized in that The PA is BO2 - , BO3 3- 、B4O7 2- 、CO3 2- 、C2O4 2- 、NO3 - 、SiO4 4- PO2 - PO3 3- PO4 3- 、P2O7 4- 、P3O 10 5- 、SO3 2- 、SO4 2- 、S2O3 2- 、S2O7 2- One or a combination of anions.
3. The composite positive electrode material according to claim 1, characterized in that: The composite positive electrode material is selected from at least one of KVPO4F / graphite, KFePO4F / graphite, and KTiPO4F / graphite.
4. The method for preparing the composite positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Mixing a transition metal source and graphite, reacting, and obtaining a product; (2) subjecting the product obtained in step (1), a polyanion monomer source, and an alkali metal ion source to a solvothermal reaction to obtain a precipitate; (3) calcining the precipitate obtained in step (2) to obtain the composite positive electrode material; In step (1), the reaction temperature is 80-1200°C.
5. The preparation method according to claim 4, characterized in that: In step (1), the transition metal source includes at least one of a titanium source, a vanadium source, a chromium source, a manganese source, an iron source, a cobalt source, a nickel source, a copper source, and a zinc source.
6. The preparation method according to claim 5, characterized in that: The titanium source comprises at least one of elemental titanium, titanium trioxide, titanium dioxide, titanium (III) sulfate, titanium (IV) sulfate, titanium phosphate, potassium fluorotitanate, hexafluorotitanic acid, tetrabutyl titanate, tetraethyl titanate, isopropyl titanate, titanium tetrachloride, titanium trichloride, titanium dihydride, ammonium fluorotitanate, titanium tetrafluoride, dichlorotitacenene, bis(acetylacetonato)isopropyl titanate or a hydrate thereof; The vanadium source comprises at least one of elemental vanadium, vanadium trioxide, vanadium dioxide, vanadium pentoxide, vanadium difluoride, vanadium trifluoride, vanadium tetrafluoride, vanadium pentafluoride, vanadium oxyfluoride, vanadium dichloride, vanadium trichloride, vanadium tetrachloride, vanadium oxychloride, vanadium dibromide, vanadium tribromide, vanadium tetrabromide, ammonium metavanadate, potassium orthovanadate, potassium metavanadate, vanadium acetylacetonate, vanadium acetylacetonate, triisopropoxy vanadium oxide, tripropanol vanadium oxide or their hydrates; The chromium source comprises at least one of elemental chromium, chromium acetate, chromium fluoride, chromium sulfate, chromium (II) chloride, chromium (III) chloride, chromium oxide, chromium nitride, chromium acetate, chromium nitrate or hydrates thereof; The manganese source comprises at least one of elemental manganese, manganese oxide, manganese dioxide, manganese tetraoxide, manganese (II) fluoride, manganese (III) fluoride, manganese (II) chloride, manganese (III) chloride, manganese bromide, manganese carbonate, manganese nitrate, manganese sulfate, manganese phosphate, manganese dihydrogen phosphate, manganese acetylacetonate, manganese formate, manganese (II) acetate, manganese (III) acetate, manganese oxalate or a hydrate thereof; The iron source comprises at least one of elemental iron, ferric oxide, ferrous oxide, ferrous hydroxide, ferric hydroxide, ferrous fluoride, ferric fluoride, ferrous chloride, ferric chloride, ferric bromide, ferric bromide, ferric formate, ferrous acetate, ferrous nitrate, ferrous sulfate, ferric nitrate, ferric sulfate, ferric acetylacetonate, ferrous oxalate, ferric oxalate or hydrates thereof; The cobalt source comprises at least one of elemental cobalt, cobalt monoxide, cobalt trioxide, cobalt tetraoxide, cobalt (II) hydroxide, cobalt (III) hydroxide, cobalt (II) fluoride, cobalt (III) fluoride, cobalt (II) chloride, cobalt (III) chloride, cobalt bromide, cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate, cobalt oxalate, hexamidocobalt chloride, cobalt acetylacetonate or their hydrates; The nickel source comprises at least one of elemental nickel, nickel oxide, nickel oxide, nickel hydroxide, nickel hydroxide, nickel fluoride, nickel chloride, nickel bromide, nickel nitrate, nickel carbonate, nickel sulfate, nickel acetate, nickel oxalate, nickel bis(hexafluoroethylacetone), nickel sulfamate, basic nickel carbonate, nickel acetylacetonate dihydrate, nickel trifluoromethanesulfonate, nickel benzenesulfonate, nickel acetylacetonate, nickel fluoroborate or a hydrate thereof; The copper source is at least one of elemental copper, cuprous oxide, cupric oxide, copper hydroxide, copper fluoride, copper chloride, copper bromide, copper carbonate, basic copper carbonate, copper nitrate, copper sulfate, copper acetate, copper oxalate, copper tartrate, copper citrate, copper fluoroborate, copper acetylacetonate, copper gluconate, copper phosphate or a hydrate thereof; The zinc source includes at least one of elemental zinc, zinc oxide, zinc hydroxide, zinc fluoride, zinc chloride, zinc bromide, zinc iodide, zinc sulfate, zinc nitrate, zinc carbonate, zinc acetate, zinc oxalate, zinc citrate, zinc fluoroborate, zinc tartrate, zinc borate, zinc metaborate, zinc acetylacetonate, zinc gluconate or a hydrate thereof.
7. The preparation method according to claim 4, characterized in that: In step (2), the polyanion monomer source includes at least one of boric acid, fluoroboric acid, potassium fluoroborate, ammonium borate, lithium carbonate, sodium carbonate, potassium carbonate, lithium nitrate, sodium nitrate, potassium nitrate, silicic acid, fluorosilicic acid, potassium fluorosilicate, phosphoric acid, lithium phosphate, sodium phosphate, potassium phosphate, sulfuric acid, lithium sulfate, sodium phosphate, potassium sulfate, oxalic acid, potassium oxalate, potassium hydrogen oxalate, ammonium oxalate, diethyl oxalate or a hydrate thereof.
8. The preparation method according to claim 4, characterized in that: In step (2), the alkali metal ion source includes at least one of a lithium source, a sodium source or a potassium source.
9. The preparation method according to claim 8, characterized in that: The lithium source comprises at least one of lithium fluoride, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium acetate, lithium salicylate, lithium acetoacetate, lithium carbonate, lithium trifluoromethanesulfonate, lithium dodecyl sulfate, lithium citrate, lithium bis(trimethylsilyl)amide, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl)imide or their hydrates; The sodium source comprises at least one of sodium chloride, sodium fluoride, sodium sulfate, sodium carbonate, sodium phosphate, sodium nitrate, sodium difluorooxalate borate, sodium pyrophosphate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, trisodium citrate, sodium metaborate, sodium borate, sodium molybdate, sodium tungstate, sodium bromide, sodium nitrite, sodium iodate, sodium iodide, sodium silicate, sodium lignin sulfonate, sodium hexafluorophosphate, sodium oxalate, sodium aluminate, sodium methane sulfonate, sodium acetate, sodium dichromate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(trifluoromethanesulfonyl)imide or a hydrate thereof; The potassium source includes at least one of potassium carbonate, potassium acetate, potassium nitrite, potassium fluoroborate, potassium bromide, potassium sulfate, potassium oxalate, potassium persulfate, potassium hydroxide, potassium pyrosulfate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium pyrosulfite, potassium pyrophosphate, potassium chromium sulfate, potassium hydrogen tartrate, potassium dichromate, potassium hydrogen phthalate, potassium hydrogen oxalate, potassium sulfite, potassium sorbate, potassium fluorosilicate, tripotassium phosphate, potassium gluconate, potassium oleate or a hydrate thereof.
10. The preparation method according to claim 4, characterized in that: When the alkali metal ion source is added in step (2), a fluorine source is also added, or before calcination in step (3), the precipitate is mixed with the fluorine source and then calcined.
11. The preparation method according to claim 10, characterized in that: The fluorine source includes at least one of potassium fluoride, sodium fluoride, lithium fluoride, potassium fluoroborate, potassium fluorosilicate, potassium tantalate, ammonium fluoroborate, diethyl fluoromalonate, potassium fluorotitanate, 3,5-difluorobenzylamine, 2,6-difluorobenzoic acid, 2-chloro-4-fluorobenzoic acid, 3-fluoro-5-bromoaniline, heptafluorobutyric acid, m-trifluoromethylcinnamoyl chloride or perfluorooctanoic acid.
12. The preparation method according to claim 4, characterized in that: In step (2), the temperature of the solvent thermal reaction is 80-280°C.
13. The preparation method according to claim 4, characterized in that: The alkali metal ion source may also be mixed with the precipitate before calcination in step (3), and then calcined.
14. The preparation method according to claim 4, characterized in that: In step (3), the calcination temperature is 350-1600°C.
15. Use of the composite positive electrode material according to any one of claims 1 to 3 in batteries, electric vehicles or energy storage power stations.
16. A secondary battery, characterized in that: The composite positive electrode material comprises the composite positive electrode material according to any one of claims 1 to 3.
17. The method for preparing a secondary battery according to claim 16, characterized in that: The following steps are involved: The composite positive electrode material is prepared into a slurry, and coated on the surface of the positive electrode current collector to obtain a positive electrode; The positive electrode and the negative electrode, the electrolyte and the separator are assembled to obtain the secondary battery.
18. The preparation method according to claim 17, characterized in that: The following steps are involved: Preparation of negative electrode: cutting metal foil to serve as negative electrode and negative electrode current collector, or mixing negative electrode active material, conductive agent and binder into slurry to prepare negative electrode active material slurry, coating the negative electrode active material slurry on the surface of negative electrode current collector, drying and cutting to obtain negative electrode; Preparing an electrolyte: mixing an alkali metal salt electrolyte with a solvent to prepare an electrolyte; Assembling the battery: Assembling the negative electrode, electrolyte, separator and positive electrode to obtain the secondary battery.
Citation Information
Patent Citations
Positive electrode material for lithium ion battery and preparation method thereof
CN109192935A
Composite positive electrode material obtained by utilizing waste lithium iron phosphate battery, method and application thereof
CN113161524A